PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG DALAM KEPAILITAN (ANALISIS TERHADAP PUTUSAN PENGADILAN NIAGA NOMOR: 20/PAILIT/2011/PN.NIAGA.SBY) - I Wayan Wesna Astara (University of Udayana, 2015)
The insolvent Debtor (PT Dwimas Andalan Bali) filed for insolvency by the Creditors (PT. Karsa Industama Mandiri) did not use his rights to submit a Delay for Debt Payment Obligations (DDPO) due to creditors have been in default and there has been an allegation of fraud in the insolvency proceedings becomes a phenomenon in the world of tourism business in Indonesia. In fact that the Debtor filed for insolvency has executed reconciliation with the other creditors, however there was no reconciliation with PT. Karsa Industama Mandiri. Therefore, the debtor has lost his opportunity to prevent insolvency through the Agency of Delay for Debt Payment Obligations (DDPO). Thus, the problems of this thesis are: what are the efforts of DDPO in insolvency mechanism? And how is the legal protection for debtor in insolvency proceedings. This research applied normative legal research method with the historical approach, legislative approach, and conceptual approach. Furthermore, the source of primary legal materials and secondary legal materials were analyzed through the measures of description, interpretation, systematization, evaluation and argumentation. The results of the research showed that the debtor (PT Dwimas Andalan Bali) as the Respondent of Insolvency has filed rebuttal that the Applicant of Insolvency has committed defaults by applying the doctrine of excptio non adimpleti cordractus and the Applicant of Insolvency (PT Industama Karsa Mandiri) was alleged of committing frauds and forgery. Therefore the insolvent debtor who should filed for insolvency to DDPO did not execute it, instead he executed reconciliation with the other creditors unless the Applicant of Insolvency. In this case, the DDPO Agency was not meaningful to the debtor and the Debtor of Insolvency reported the Applicant of Insolvency to the Regional Police of Bali. Related to the legal protection of debtor under the Law of Insolvency and DDPO No. 37 of 2004, there has been no principle reflected to provide equal protection for all relevant parties concerned against one's or company's insolvency